IMPLEMENTASI MANAJEMEN KRITERIA KETUNTASAN MINIMAL (KKM) DI SMK NASIONAL AL-HUDA PEKANBARU - ARDIL ARDIL; MASHADI MASHADI; SUMARDI SUMARDI (Universitas Riau, 2017)
This research is motivated by disbelief the community on the report whichreceived by students, the peoples thought that the school only able to provide high value tostudents without followed by capability of being higher too.The result of this assessmentsystem the students do not know where their talents , teachers dishonest again in give anassessment, and parents do not know where the advantages and disadvantages of children inmastering lessons. This research conducted at vocational high school National Al-hudaPekanbaru, with the method the qualitative study, to technique collecting data is triangulationthat are: observation, Interviews and documentation. The result of rcsearch explain that thedetermination of criteria completeness minimal at vocational high school National Al-hudaPekanbaru less aspect complexity, capacity and intake owned vocational high schools NationalAl-huda Pekanbaru, so that the determination of criteria completeness minimal at vocationalhigh school national al-huda less quality. Recommendations of study are : 1 the educationoffice to conduct evaluation of criteria completeness minimal set by schools. 2 the teachersshould give the students value objective and honest accordance with students ability, that studentscan know where advantages and rest in mastering lessons.